Correlation between Clinical, Operative and Histopathological Findings of Adnexal Masses – A Study of 50 Cases - Rahman, Dilara; Jahan, Afia Akhter; Akter, Asma; Parvin, Mossammat Tahmina; Mile, Jasrin Akter; Rouf, Salma (Central Medical College Journal, 2023)
Background: Adnexal mass has multidimensional diagnosis that may be related to fallopian tube, ovary etc. These masses may be benign, intermediate and malignant. The ability of clinical approach to diagnose the exact pathology of adnexal mass is still a question. Objective: To explore the correlation of clinical findings with operative and histopathological findings of adnexal masses. Method and Materials: A prospective and observational study was conducted in a tertiary hospital during the period of July 2015 to December 2015. 69 patients were selected according to purposive sampling and further scrutinized according to selection criteria, which were clinically diagnosed as adnexal mass. All the 50 patients undergone surgical intervention followed by histopathology. All the patients’ data were recorded through a semi-structured data collection sheet. Result: Study shows clinical and post-operative (per-operative + histopathology) findings of adnexal masses were 54% vs 50% for ovarian endometrioma, 24% vs 22% for benign ovarian tumor and 22% vs 26% for other adnexal masses respectively. Conclusion: Clinical findings with the help of sonography can guide effectively to the diagnosis of adnexal masses. However, per-operative and histopathological findings are required for the confirmation. Central Medical College Journal Vol 6 No 2 Jauly 2022 Page: 62-66